Improvement of foreign language teaching methodology through modern pedagogical approaches - Xasanova Madina (Genius Journals, 2023)
The role of modern pedagogical technologies in the field of education is discussed in this article. How education is developing step by step in keeping with the times, as well as the analysis of current problems and shortcomings of the foreign language teaching methodology is highlighted
Keywords: universal; universallinguistics; experimental